DEVELOPMENT OF SMART ANTI-CORROSION COATINGS WITH METAL ION END CAPPED NANOCONTAINER LOADED WITH SINGLE AND DUO GREEN CORROSION INHIBITORS - SURESH KUMAR, SUBHALAKSHMI (2021)
The cost incurred by the direct and indirect damages of corrosion are immense. Even if we apply all the control measures available to prevent corrosion, it is not possible to cut down the damage completely. Hence, new and efficient methods to prevent corrosion are in demand. The objective of the current work is to synthesize a smart coating that is not only efficient but also environmentally friendly. For the first time, two green corrosion inhibitors are loaded into the halloysite nanotubes and end capped using metal ions. Vanillin and thyme oil were loaded individually and together into halloysite nanotubes and was end capped using copper ions to form VHNTES, THNTES, and VTHNT-ES. The loading of the halloysite nanotubes with the green corrosion inhibitors were characterized by ultraviolet visible spectroscopy (UV-vis) and confirmed by the characteristic peaks in the spectrum obtained from fourier-transform infrared (FTIR) spectroscopy.